Rainfed farming systems - Tow, Philip; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
While agriculturists need a good grasp of the many separate aspects of agriculture, it is essential that they also understand the functioning of farming systems as a whole and how they can be best managed. This book takes such a combined approach. It analyses common rainfed farming systems around the world and discusses both their strengths and ways of improving their operation and management for long term productivity, profitability and sustainability. For such desirable outcomes, the components of a system must operate together efficiently, through an understanding of the effects of external influences and inputs and of relevant interactions and other relationships. Using relevant agricultural principles and the understanding of a wide range of rainfed farming systems, this book defines principles and practices important to the effective operation and management of such systems. This is done in the context of many challenges for agriculture: climatic variability and long term climatic change; degradation of most agricultural soils; spread of diseases, pests and weeds, rapid innovations in technology and the interaction of market and political forces at both local and global levels.
Preface -- Foreword -- 1. Principles of a Systems Approach to Agriculture -- 2. Types of Rainfed Farming Systems Around the World -- 3. A Systems Approach to Climate Risk in Rainfed Farming Systems -- 4. Water Availability and Use in Rainfed Farming Systems --  5. Plant Nutrient Management in Rainfed Farming Systems -- 6. Principles and Management of Soil Biological Factors for Sustainable Rainfed Farming Systems -- 7. Technological Change in Rainfed Farming Systems -- 8. Weed Management in Rainfed Agricultural Systems -- 9. Principles and Methods for Sustainable Disease Management in Rainfed Agricultural Systems -- 10. Sustainable Pest Management in Rainfed Farming Systems -- 11. Interactions Between Crop and Livestock Activities in Rainfed Farming Systems -- 12. Economic and Social Influences on the Nature, Functioning and Sustainability of Rainfed Farming Systems -- 13. Farming Systems Design -- 14. Soil Organic Carbon ? Role in Rainfed Farming Systems -- 15. Rainfed Farming Systems in the West Asia-North Africa (WANA) Region -- 16. Rainfed Farming Systems in South Africa -- 17. Farming Systems, Emerging Farmers and Land Reform in the Limpopo Province of South Africa -- 18. Modernisation of Eritrean Rainfed Farming Systems Through a Conservation Farming Systems Approach -- 19. Rainfed Farming Systems on the Canadian Prairies -- 20. Rainfed Farming Systems in the USA -- 21. Rainfed Agroecosystems in South America -- 22. Important Rainfed Farming Systems of South Asia -- 23. Rainfed Farming Systems in the Loess Plateau of China -- 24. Farming Systems in the Valleys of Central Tibet -- 25. Rainfed Farming Systems of North-Eastern Australia -- 26. Diversity and Evolution of Rainfed Farming Systems in southern Australia -- 27. Using Monitoring and Evaluation for Continuous Improvement of Rainfed Farming Systems -- 28. More from Less ? Improvements in Precipitation Use Efficiency in Western Australian Wheat Production -- 29. Transforming Farming Systems: Expanding the Production of Soybeans in Ontario -- 30. The Social Dimensions of Mixed Farming Systems -- 31. A Study in the Development of a Farm System on the Canadian Prairies -- 32. Improving Traditional Crop-Pasture Farming Systems with Lucerne South Eastern Australia -- 33. Use of Conservation Agriculture to Improve Farming Systems in Developing Countries -- 34. Using Conservation Agriculture and Precision Agriculture to Improve a Farming System -- 35. Risk Management Strategies and Decision Support Systems in Agriculture -- 36. The Emergence of ?Farming Systems? Approaches to Grains Research, Development and Extension -- 37. Farmer Decision-Making in Rainfed Farming Systems -- 38. When Culture and Science Meet, the Tension Can Mount -- 39. Advances in No-Till Farming Technologies and Soil Compaction Management in Rainfed Farming Systems -- 40. No-Tillage Agriculture in West Asia & North Africa -- 41. A Comparison of Three Farms in South Australia -- 42. Ruradene, South Australia -- 43. Lindene -- 44. Developments in a Mixed Farming System in Southern New South Wales, Australia -- 45. The Development and Operation of No-Till Farming in Northern New South Wales (NSW), Australia -- 46. Farming System Development in North-Central Victoria -- 47. The Jochinke Farm; David Jochinke -- 48. The Halford Farm -- 49. Four Farms in the USA -- 50. Summing Up -- Glossary -- Index.
Electronic reproduction.
Keywords: Dry farming; Agriculture; Electronic books